RESPON PERTUMBUHAN DAN HASIL CABAI RAWIT TERHADAP SUBTITUSI PUPUK KANDANG AYAM DENGAN BOKASHI KIRINYUH - Sudarno Sudarno; Gusti Rusmayadi; Joko Purnomo (Universitas Lambung Mangkurat, 2019)
Cayenne pepper by including the horticulture and fruit very popular community.The research was carried out in a site faculty agriculture, Kel. Big river, Kec .Banjarbaru south in July 2018 - November 2018. Research in flats in the design environmental factors random complete singular to 6 standard 4 times test. Treatment consisting of : without fertilizer (s0), 100 % chicken cages (s1), 75 % chicken cages + 25 % bokashi is siam weed (s2), 50 % chicken cages + 50 % bokashi is siam weed (s3), 25 % chicken cages + 75 bokashi is siam weed (s4), 100 % bokashi is siam weed (s5).The results showed the subtitusi manure chicken + bokashi kirinyuh influential real against tall plant at the age of 42 days.Trunk diameter at the age of 28 days, 35 day, 42 days, flowering age, the number of fruit per plants, heavy 100 seeds, the yield of fruit per plants and the per hectare. But it does not affect tall plant at the age of 14 days, 21 days, 28 days, 35 day, trunk diameter at the age of 14 ha